Investigating the Correlation between Social Health, Academic Motivation, and Academic Status among Students of Abadan University of Medical Sciences - Jamshid Bahmaei; Bagher Pahlavanzadeh; Yasaman Azaraeen; Ebrahim Kharazinejad (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: Paying attention to students' growth and academic progress and the related affecting factors are among the necessary strategies to improve education. Students' social health can increase their performance in various fields, including academic motivation and academic progress. Therefore, this study was designed and implemented to investigate the role of social health in the motivation and academic progress of students at Abadan University of Medical Sciences, Abadan, Iran. Methods: The present study was descriptive, analytical, and cross-sectional. The study samples (n=260) were the students of Abadan University of Medical Sciences. The data collection tools included a demographic characteristics form, the Social Health Questionnaire, the Academic Motivation Questionnaire, and the overall grade point average as a measure of academic progress. Data were analyzed at a significance level of 0.05 using SPSS 26 statistical software. Results: The results of the study showed that in general,  there was no significant correlation between social health and grade point average (academic progress) (P<0.05). It was also found that academic motivation and its components had no significant correlation with academic progress (P<0.05), except for the lack of motivation, which had a significant positive correlation with age and a significant negative correlation with academic achievement (P<0.05). A significant positive correlation was found between social health and academic motivation (r=0.457, P<0.001). Conclusion: Based on the results, students considered the presence and participation in social groups, as well as their desire and motivation to attend university, independent of academic progress. According to these students, establishing social relationships and interacting with others was the motivation for attending university.